Effects of Customer Knowledge Management on Marketing Management and Results: Case Study in Business Companies, FARS - Hosseinifard, Seyedmohammad; Tohidi, Fateme; Jahromi, Hamidreza Abootalebi; Jahromi, Navid Abootalebi; Adib, Nakisa; Ayoubi, Abdolhossein (European Scientific Journal, ESJ, 2020)
The purpose of the present study was to investigate the impact of customer knowledge management on marketing management and marketing results in Fars business companies. Statistical population of the present research includes 1135 employees and managers of Fars business companies which with using formula, 290 individuals were questioned with random sampling. To collect data, standard questionnaires including Vorhies & Morgan’s (2005) marketing questionnaire, Ling-Yee’s (2005) marketing management questionnaire, Alegri’s (2011) knowledge management questionnaire were used. In order to confirm their reliability, their coefficient Cronbach’s alphas are respectively 0.82, 0.79 and 0.88. For data analysis, inferential statistics, Pearson correlation test, Single variable regression, Path analysis and SPSS software version 22 were used. The results showed that there is a positive and meaningful relationship between customer knowledge management, marketing results(efficiency) and marketing management. Also, knowledge management had a positive and significant impact on marketing management and marketing results. Moreover, proposed conceptual model is supported.